The mirror image of the curve \[\arg \left( {\dfrac{{z + i}}{{z - 1}}} \right) = \dfrac{\pi }{4},i = \sqrt { - 1} \] in the line \[x - y = 0\] is
A.\[\arg \left( {\dfrac{{z + i}}{{z + 1}}} \right) = \dfrac{\pi }{4}\]
B.\[\arg \left( {\dfrac{{z + 1}}{{z - i}}} \right) = \dfrac{\pi }{4}\]
C.\[\arg \left( {\dfrac{{z - i}}{{z + 1}}} \right) = \dfrac{\pi }{4}\]
D.\[\arg \left( {\dfrac{{z + i}}{{z - 1}}} \right) = \dfrac{\pi }{4}\]
Answer
Verified
463.2k+ views
Hint: First of all find the locus represented by the curve. And then we will find the mirror image along the given line. We know that a complex number is \[z = x + iy\] using this find the locus.
Complete step-by-step answer:
Given that,
\[\arg \left( {\dfrac{{z + i}}{{z - 1}}} \right)\] but a complex number is written as \[z = x + iy\].
So write the curve given above in complex number form as
\[ \Rightarrow \dfrac{{z + i}}{{z - 1}} = \dfrac{{x + iy + i}}{{x + iy - 1}}\]
Taking i common in numerator, and writing real and imaginary part as in complex number
\[ \Rightarrow \dfrac{{x + \left( {y + 1} \right)i}}{{\left( {x - 1} \right) + iy}}\]
Now to simplify the terms we will multiply numerator and denominator by \[\left( {x - 1} \right) - iy\]
\[ \Rightarrow \dfrac{{x + \left( {y + 1} \right)i}}{{\left( {x - 1} \right) + iy}} \times \dfrac{{\left( {x - 1} \right) - iy}}{{\left( {x - 1} \right) - iy}}\]
Now multiply the terms in numerator and denominator will be \[{a^2} - {b^2} = \left( {a + b} \right)\left( {a - b} \right)\]
\[ \Rightarrow \dfrac{{x\left( {x - 1} \right) - xyi + \left( {y + 1} \right)\left( {x - 1} \right)i - \left( {y + 1} \right)y{i^2}}}{{{{\left( {x - 1} \right)}^2} - {{\left( {iy} \right)}^2}}}\]
Since \[{i^2} = - 1\] second term of denominator changes to
\[ \Rightarrow \dfrac{{x\left( {x - 1} \right) - xyi + \left( {y + 1} \right)\left( {x - 1} \right)i + \left( {y + 1} \right)y}}{{{{\left( {x - 1} \right)}^2} + {y^2}}}\]
Multiplying the terms in numerators and separating the real and imaginary parts
\[ \Rightarrow \dfrac{{{x^2} - x + {y^2} + y + i\left( {xy - y + x - 1} \right) - xy)}}{{{{\left( {x - 1} \right)}^2} + {y^2}}}\]
The terms xy cancels here and we get
\[ \Rightarrow \dfrac{{{x^2} - x + {y^2} + y + i\left( {x - y - 1} \right)}}{{{{\left( {x - 1} \right)}^2} + {y^2}}}\]
Now here we separated the real and imaginary terms.
Given that
\[\arg \left( {\dfrac{{z + i}}{{z - 1}}} \right) = \dfrac{\pi }{4}\]
In this case real and imaginary parts are the same. So equating them,
\[ \Rightarrow \dfrac{{{x^2} - x + {y^2} + y}}{{{{\left( {x - 1} \right)}^2} + {y^2}}} = \dfrac{{\left( {x - y - 1} \right)}}{{{{\left( {x - 1} \right)}^2} + {y^2}}}\]
Cancelling the denominators from both the sides
\[ \Rightarrow {x^2} - x + {y^2} + y = x - y - 1\]
\[ \Rightarrow {x^2} - x + {y^2} + y - x + y + 1 = 0\]
Adding x and y terms,
\[ \Rightarrow {x^2} + {y^2} - 2x + 2y + 1 = 0\]
Now if we observe this is the locus of a circle with center \[\left( {1, - 1} \right)\].
It can be plotted as ,
Now since the locus of light blue circle is the mirror image of the curve. Thus the curve is given as
\[\arg \left( {\dfrac{{z - i}}{{z + 1}}} \right) = \dfrac{\pi }{4}\].
Hence option C is the correct answer.
Note: Students generally make mistakes when we simplify the fraction with the help of complex conjugate of term in denominator. So take the simplification term carefully. And the mirror image of the curve is along the line x=y so draw that line to get an exact idea of the mirror locus.
Complete step-by-step answer:
Given that,
\[\arg \left( {\dfrac{{z + i}}{{z - 1}}} \right)\] but a complex number is written as \[z = x + iy\].
So write the curve given above in complex number form as
\[ \Rightarrow \dfrac{{z + i}}{{z - 1}} = \dfrac{{x + iy + i}}{{x + iy - 1}}\]
Taking i common in numerator, and writing real and imaginary part as in complex number
\[ \Rightarrow \dfrac{{x + \left( {y + 1} \right)i}}{{\left( {x - 1} \right) + iy}}\]
Now to simplify the terms we will multiply numerator and denominator by \[\left( {x - 1} \right) - iy\]
\[ \Rightarrow \dfrac{{x + \left( {y + 1} \right)i}}{{\left( {x - 1} \right) + iy}} \times \dfrac{{\left( {x - 1} \right) - iy}}{{\left( {x - 1} \right) - iy}}\]
Now multiply the terms in numerator and denominator will be \[{a^2} - {b^2} = \left( {a + b} \right)\left( {a - b} \right)\]
\[ \Rightarrow \dfrac{{x\left( {x - 1} \right) - xyi + \left( {y + 1} \right)\left( {x - 1} \right)i - \left( {y + 1} \right)y{i^2}}}{{{{\left( {x - 1} \right)}^2} - {{\left( {iy} \right)}^2}}}\]
Since \[{i^2} = - 1\] second term of denominator changes to
\[ \Rightarrow \dfrac{{x\left( {x - 1} \right) - xyi + \left( {y + 1} \right)\left( {x - 1} \right)i + \left( {y + 1} \right)y}}{{{{\left( {x - 1} \right)}^2} + {y^2}}}\]
Multiplying the terms in numerators and separating the real and imaginary parts
\[ \Rightarrow \dfrac{{{x^2} - x + {y^2} + y + i\left( {xy - y + x - 1} \right) - xy)}}{{{{\left( {x - 1} \right)}^2} + {y^2}}}\]
The terms xy cancels here and we get
\[ \Rightarrow \dfrac{{{x^2} - x + {y^2} + y + i\left( {x - y - 1} \right)}}{{{{\left( {x - 1} \right)}^2} + {y^2}}}\]
Now here we separated the real and imaginary terms.
Given that
\[\arg \left( {\dfrac{{z + i}}{{z - 1}}} \right) = \dfrac{\pi }{4}\]
In this case real and imaginary parts are the same. So equating them,
\[ \Rightarrow \dfrac{{{x^2} - x + {y^2} + y}}{{{{\left( {x - 1} \right)}^2} + {y^2}}} = \dfrac{{\left( {x - y - 1} \right)}}{{{{\left( {x - 1} \right)}^2} + {y^2}}}\]
Cancelling the denominators from both the sides
\[ \Rightarrow {x^2} - x + {y^2} + y = x - y - 1\]
\[ \Rightarrow {x^2} - x + {y^2} + y - x + y + 1 = 0\]
Adding x and y terms,
\[ \Rightarrow {x^2} + {y^2} - 2x + 2y + 1 = 0\]
Now if we observe this is the locus of a circle with center \[\left( {1, - 1} \right)\].
It can be plotted as ,
Now since the locus of light blue circle is the mirror image of the curve. Thus the curve is given as
\[\arg \left( {\dfrac{{z - i}}{{z + 1}}} \right) = \dfrac{\pi }{4}\].
Hence option C is the correct answer.
Note: Students generally make mistakes when we simplify the fraction with the help of complex conjugate of term in denominator. So take the simplification term carefully. And the mirror image of the curve is along the line x=y so draw that line to get an exact idea of the mirror locus.
Recently Updated Pages
Class 11 Question and Answer - Your Ultimate Solutions Guide
Master Class 11 English: Engaging Questions & Answers for Success
Master Class 11 Computer Science: Engaging Questions & Answers for Success
Master Class 11 Maths: Engaging Questions & Answers for Success
Master Class 11 Social Science: Engaging Questions & Answers for Success
Master Class 11 Economics: Engaging Questions & Answers for Success
Trending doubts
10 examples of friction in our daily life
What problem did Carter face when he reached the mummy class 11 english CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Proton was discovered by A Thomson B Rutherford C Chadwick class 11 chemistry CBSE